Concurrent HPV-related oropharyngeal carcinoma in four couples. (November 2018) - Sathasivam, Hans Prakash; Bhatia, Ramya; Bradley, Paula; Robson, Andrew; Paleri, Vinidh; Cocks, Helen; Oozeer, Nashreen; Milne, Debra; Sloan, Philip; Robinson, Max
Highlights: Natural history of HPV-related oropharyngeal squamous cell carcinoma is an enigma. HPV-related oropharyngeal carcinoma in couples suggests transmission of HPV16. Occurrence of HPV-related oropharyngeal squamous cell carcinoma in couples is rare. Abstract: Objectives: Typically, HPV-related cancers are sexually transmitted, however, the natural history of HPV-related oropharyngeal squamous cell carcinoma (OPSCC) is unclear. HPV16 transmission has been reported previously between five couples with OPSCC. We report the clinico-pathological features of a further four couples with HPV-related OPSCC and compare them with the published cases. Patients and methods: We identified four couples in long-term heterosexual relationships that all had HPV-related OPSCC. The couples were treated at three UK hospitals and presented between 2009 and 2015. HPV tests included p16 immunohistochemistry, high-risk HPV DNA in-situ hybridisation and Roche Cobas HPV test. DNA sequencing was used to determine the HPV variant. Results: The four couples represented < 2% of patients with HPV-related OPSCC at the three contributing hospitals (8 of 457 consecutive patients). The couples' tumours all contained HPV16. The mean age was 63 years old (range 52–72 years). The interval between the index cancer and the partner's cancer was 16, 24, 26 and 64 months respectively. The majority of patients had Stage I disease (UICC TNM8). Six of eight patients are disease free, one patient is alive with disease and there was one death from loco-regional recurrence. Conclusion: This report highlights the occurrence of HPV-related OPSCC in heterosexual couples and raises the possibility of transmission of HPV16. Despite increasing prevalence of HPV-related OPSCC and increased awareness of the disease, there is a paucity of couples with the disease, suggesting either under-reporting or that the development of OPSCC following HPV transmission between couples is a rare event.